The Function of FGF Signaling in the Lens Placode - Garcia, Claudia M. (2011)
Previous studies suggested that FGF signaling is important for lens formation. However, the times at which FGFs act to promote lens formation, the FGFs that are involved, the cells that secrete them and the mechanisms by which FGF signaling may promote lens formation are not known. We found that transcripts encoding several FGF ligands and the four classical FGF receptors are detectable in the lens-forming ectoderm at the time of lens induction. Conditional deletion of Fgfr1 and Fgfr2 from this tissue resulted in the formation of small lens rudiments that soon degenerated. Lens placodes lacking Fgfr1 and 2 were thinner than in wild type embryos. Deletion of Fgfr2 increased cell death from the initiation of placode formation and concurrent deletion of Fgfr1 enhanced this phenotype. Fgfr1/2 conditional knockout placode cells expressed lower levels of proteins known to be regulated by FGF receptor signaling, but proteins known to be important for lens formation were present at normal levels in the remaining placode cells, including the transcription factors, Pax6, Sox2 and FoxE3 and the lens-preferred protein, αA-crystallin. Previous studies identified a genetic interaction between BMP and FGF signaling in lens formation and conditional deletion of Bmpr1a caused increased cell death in the lens placode, resulting in the formation of smaller lenses. In the present study, conditional deletion of both Bmpr1a and Fgfr2 increased cell death beyond that seen in Fgfr2(CKO) placodes and prevented lens formation. These results suggest that the primary role of autocrine or paracrine FGF signaling is to provide essential survival signals to lens placode cells. Because apoptosis was already increased at the onset of placode formation in Fgfr1/2 conditional knockout placode cells, FGF signaling was functionally absent during the period of lens induction by the optic vesicle. Since the expression of proteins required for lens formation was not altered in the knockout placode cells, we can conclude that FGF signaling from the optic vesicle is not required for lens induction.